Trends in employment and hospitalisation in patients with Sjogren’s syndrome 1996-2016: results from the German National database - Callhoff, J.; Thiele, K.; Dorner, T.; Zink, A.; Richter, J. G.; Henes, J.; Albrecht, K. (Clin Exp Rheumatol, 2019)
OBJECTIVES: To assess trends in treatments and outcomes in patients with primary Sjogren’s syndrome (pSS), focusing on employment, hospitalisation and medical treatment in the past two decades. METHODS: From 1996 to 2016, approximately 300 patients with pSS were annually documented in the National Database of the German Collaborative Arthritis Centres. Data on treatment, physicians’ assessments of disease activity, patient-reported outcomes, hospitalisation and employment were collected and compared to patients with rheumatoid arthritis (RA), matched 1:1 for age, sex and disease duration for each calendar year. RESULTS: Patients with pSS (>90% female, age 44 years at disease onset, disease duration 10 years) were more frequently assessed to be in low disease activity in 2016 (93%) than in 1996 (62%), p<0.01. Treatment with antimalarials increased from 1996 to 2016 (31 to 50%, p<0.01) and less patients were on glucocorticosteroids (50 to 34%, p<0.01) but <5% were treated with biologics. Employment (<65 years) increased by 21 percentage points (43 to 64%, p<0.001), exceeding the increase observed for RA patients (+15 percentage points). Early retirement (22 to 10%, p=0.01), hospitalisation/year (13 to 7%, p=0.08) and sick leave (39% in 1997 to 27%, p=0.09) decreased comparably to RA patients. CONCLUSIONS: Overall, similar trends were observed for RA and pSS cohorts despite minor changes in pSS therapy. Work participation has improved significantly over two decades in pSS. A greater perception of pSS without systemic manifestations may have caused a shift towards less severely affected patient cohorts today.